Teaching Australian Aboriginal higher education students: what should universities do?. Issue 11 (2nd November 2017) - Rochecouste, Judith; Oliver, Rhonda; Bennell, Debra; Anderson, Roz; Cooper, Inala; Forrest, Simon
Abstract : This paper reports findings from a recent study of Australian Aboriginal higher education student experience. Reported here are extracts from a set of case studies of staff, specifically those working in Indigenous Centres, involved with these students in both teaching and support capacities. These participants provided a rich set of qualitative data regarding their own experiences in the learning and teaching of Australian Aboriginal students. The paper raises important issues for the improvement of Aboriginal and Torres Strait Islander university student experience and for increasing their representation in higher education, a strategy strongly supported by several current government initiatives. Best practice in the context of this paper not only includes teaching and learning, which in turn has implications for raising the awareness of university teaching staff, but also applies more broadly at the level of university-wide responsibility including policy-making and future directions.